Enterprise risk management model towards hospital performance through mediating role of business model innovation - Mohamed Hussain Rahmatalla Almaazmi, Fatima (2025)
The healthcare sector in the UAE operates within a complex regulatory environment that necessitates effective Enterprise Risk Management (ERM) strategies to ensure financial sustainability, operational efficiency, and enhanced patient care. Despite the growing emphasis on risk management, limited research has explored its indirect effects on hospital performance through Business Model Innovation (BMI) and the moderating influence of stakeholder engagement. This study addresses this gap by examining the relationship between ERM and hospital performance, investigating BMI as a mediating factor, and assessing the role of stakeholder engagement in strengthening this relationship. Grounded in the Resource-Based View (RBV) and Agency Theory, this research positions ERM as a strategic capability that enhances hospital resilience while addressing information asymmetries between administrators and stakeholders. A quantitative research design was employed, utilizing survey responses from 227 hospital managers across private, general, and specialist hospitals in the UAE. The findings confirm that ERM significantly enhances hospital performance, particularly in financial and operational aspects, but does not directly drive business model innovation. Instead, BMI fully mediates the ERM-performance link, highlighting the importance of strategic innovation in maximizing ERM benefits. Additionally, stakeholder engagement positively moderates the ERM-BMI relationship, emphasizing the role of collaborative governance in fostering innovation. These insights contribute to the theoretical discourse by extending RBV and Agency Theory to the healthcare sector, demonstrating how risk management capabilities, innovation, and stakeholder participation collectively enhance hospital outcomes. From a practical standpoint, the study underscores the need for UAE hospitals to integrate ERM with innovation strategies and stakeholder collaboration to navigate regulatory challenges and optimize healthcare delivery. Policymakers should foster environments that encourage risk-informed innovation while ensuring compliance with national healthcare objectives. However, the study’s reliance on cross-sectional survey data and self-reported managerial perspectives presents limitations, warranting future longitudinal research to assess the evolving impact of ERM on hospital performance. Future research should also explore multi-stakeholder perspectives, digital transformation in risk management, and the varying influence of different stakeholders in ERM implementation. By advancing both theoretical and practical insights, this study offers a comprehensive framework for enhancing hospital resilience and sustainability in the UAE’s dynamic healthcare landscape.